Analysis of compost repair mortars by vinylic copolymer, PVA, and SBR - de Souza, Mateus Henrique; de Souza, Rafael Alves (Revista ALCONPAT, 2019)
This work has as its objective the development and analysis of compostable polymeric mortars using vinyl copolymer, PVA (polyvinyl acetate) and SBR (styrene-butadiene). Tests were carried out to determine the compressive and diametral compression tensile strengths. In addition, the adhesive strength between the repair and the concrete was determined by means of a diametral compression traction test. Among the materials tested, it was noticed that the material modified by SBR had the best performance, especially with respect to the adhesion to the concrete. In general, the results show that modified polystyrene hair hairs can be used to repair material.